Acyclovir is activated into a HIV-1 reverse transcriptase inhibitor in herpesvirus-infected human tissues. - Lisco,A; Vanpouille,C; Tchesnokov,EP; Grivel,J-C; Biancotto,A; Brichacek,B; Elliott,J; Fromentin,E; Shattock,R; Anton,P; Gorelick,R; Balzarini,J; et al. (Cell Host Microbe, 2008)
For most viruses, there is a need for antimicrobials that target unique viral molecular properties. Acyclovir (ACV) is one such drug. It is activated into a human herpesvirus (HHV) DNA polymerase inhibitor exclusively by HHV kinases and, thus, does not suppress other viruses. Here, we show that ACV suppresses HIV-1 in HHV-coinfected human tissues, but not in HHV-free tissue or cell cultures. However, addition of HHV-6-infected cells renders these cultures sensitive to anti-HIV ACV activity. We hypothesized that such HIV suppression requires ACV phosphorylation by HHV kinases. Indeed, an ACV monophosphorylated prodrug bypasses the HHV requirement for HIV suppression. Furthermore, phosphorylated ACV directly inhibits HIV-1 reverse transcriptase (RT), terminating DNA chain elongation, and can trap RT at the termination site. These data suggest that ACV anti-HIV-1 activity may contribute to the response of HIV/HHV-coinfected patients to ACV treatment and could guide strategies for the development of new HIV-1 RT inhibitors.